2019
DOI: 10.1001/jamapediatrics.2019.3089
|View full text |Cite
|
Sign up to set email alerts
|

Chronotype, Social Jet Lag, and Cardiometabolic Risk Factors in Early Adolescence

Abstract: and quality increase the risk of obesity. Sleep timing, while less studied, is important in adolescents because increasing evening preferences (chronotypes), early school start times, and irregular sleep schedules may cause circadian misalignment. OBJECTIVE To investigate associations of chronotype and social jet lag with adiposity and cardiometabolic risk in young adolescents. DESIGN, SETTING, AND PARTICIPANTS Starting in 1999, Project Viva recruited pregnant women from eastern Massachusetts. Mother-child in-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
96
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(105 citation statements)
references
References 38 publications
6
96
1
2
Order By: Relevance
“…The findings extend previously published data demonstrating association of evening chronotype with increased cardio-metabolic risk [62][63][64][65] . Our results are in agreement with a recently published study in young subjects showing association between late chronotype and BMI in female, but not male, adolescents 66 .…”
Section: Geographic and Settlement Size Analyses Of The Association supporting
confidence: 94%
“…The findings extend previously published data demonstrating association of evening chronotype with increased cardio-metabolic risk [62][63][64][65] . Our results are in agreement with a recently published study in young subjects showing association between late chronotype and BMI in female, but not male, adolescents 66 .…”
Section: Geographic and Settlement Size Analyses Of The Association supporting
confidence: 94%
“…Greater SJL is also associated with poorer sleep quality, but this association is weaker than that with chronotype and on sub-group analysis, is observed only in younger males. There are suggestions in the literature that sex may moderate the effects of SJL on various health parameters; for example, Cespedes Feliciano et al [13] recently demonstrated that adiposity was associated with social jetlag in adolescent girls but not boys. It is not currently clear what mechanisms might underpin the differential sex effects of SJL on various psychological and physiological outcomes, but hormonal differences and gendered differences in affective and other psychosocial parameters are plausible factors of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, modern humans' lifestyle and the way humans organize their sleeping and eating activities (either by choice or necessity) is such that it often leads to violation and major misalignments of circadian rhythm, leading to increased risks for serious metabolic disturbances and diseases of modern time, including obesity, diabetes, hyperlipidemia, and metabolic syndrome [79]. For example, even adolescent girls with evening chronotypes and social jet lag showed greater obesogenic phenotypes, compared to their normal-morning chronotype counterparts, despite that the duration of sleep was taken into account [81].…”
Section: Misalignments Of Circadian Rhythmmentioning
confidence: 99%